Characterization of chemically treated Ti-Zr system alloys for dental implant application - Cordeiro, Jairo M.; Faverani, Leonardo P. [UNESP]; Grandini, Carlos R. [UNESP]; Rangel, Elidiane C. [UNESP]; da Cruz, Nilson C. [UNESP]; Nociti Junior, Francisco H.; Almeida, Amanda B.; Vicente, Fabio B.; Morais, Bruna R.G. [UNESP]; Barão, Valentim A.R.; Assunção, Wirley G. [UNESP] (Elsevier, 2018)
Materials and surfaces developed for dental implants need to withstand degradation processes that take place in the oral cavity. Therefore, the aim of the study was to develop and evaluate the topographical, mechanical, chemical, electrochemical and biological properties of Ti-xZr alloys (x = 5, 10, and 15 wt%) with two surface features (machined and double acid etched). Commercially pure titanium (cpTi) and Ti-6Al-4V alloy were used as controls. Surface characterization was performed using dispersive energy spectroscopy, X-ray diffraction, scanning electron microscopy, atomic force microscopy, profilometry and surface energy. The mechanical properties were assessed using Vickers microhardness, elastic modulus and stiffness. The electrochemical behavior analysis was conducted in a body fluid solution (pH 7.4). In addition, MC3T3-E1 cells were used to determine the impact of material and surface treatment on cell morphology by SEM analysis. Data were analyzed by two-way ANOVA and Bonferroni test (α = 0.05). Ti-Zr alloys showed lower surface roughness, elastic modulus and stiffness, as well as higher hardness and surface energy when compared to cpTi. Ti-Zr system increased the polarization resistance values and significantly decreased the capacitance, corrosion current density (icorr), and passivation current density (ipass) values. The acid treatment increased the resistance and corrosion potential of the oxide layer. SEM data analysis demonstrated that Ti-Zr alloys displayed normal cell attachment/spreading and slightly changed cell morphology in the double etched surface. In conclusion, Zr addition and surface treatment altered surface, mechanical, biological and electrochemical properties of Ti material.
Keywords: Alloys; Corrosion; Dental implant; Titanium; Zirconium